Deteksi Kebocoran Kapal : Desain Dan Monitoring - Sutrisno, Viki Ananta; Adi Mulyadi; Muhammad Zainal Roisul Amin (Journal Electric Field, 2024)
This paper discusses the design and monitoring system of ship leakage. Ship leakage causes accidents at sea. Therefore, a prototype design and monitoring system are proposed. The design uses fiberglass and resin with dimensions of 60x15x13 cm, and monitoring uses the Internet of Things to turn on three automatic pumps alternately. The results show that monitoring pump 1 obtained an average water volume of 0.00131 m3, time 83.92 seconds, discharge 0.0000157 m3/second, current 0.44 A and power 2.2 W. Pump 2 obtained an average water volume of 0.00161 m3, time 139.08 seconds, discharge 0.0000116 m3/second, current 0.24 A and power 1.2 W. While pump 3 obtained an average water volume of 0.00126 m3, time 52.26 seconds, discharge 0.0000241 m3/second, current 0.68 A and power 3.4 W. The monitoring results have different average water volume, time, discharge, current and power.